Meningkatkan kemampuan mahasiswa dalam membuat RPP melalui penerapan model pembelajaran project based learning - Adi Nurjaman; Ratni Purwasih; Indah Puspita Sari (Universitas Mercu Buana Yogyakarta, 2018)
This study aims to determine the response of students to the implementation of learning-based project learning model to determine the student's ability to develop RPP through the application of learning-based project learning model and student response in project based learning learning between experimental class and control class. This research method is quasi experimental method with pretset-posttest control group design design. The study population is all students of STKIP Siliwangi who follow the course of High School Mathematics Learning Planning in the even semester of the academic year 2016/2017 consisting of 3 classes, namely: B1, B2, and B3. For the sample of the study, two classes were selected from the study population, selected B1 class as a control class consisting of 40 students and B2 class as experimental class consisting of 43 students. The sample is selected not random class. Data analysis was done to the difference of mean of student ability test result in preparing RPP and percentage from questionnaire of student response to learning of project based learning. The results showed that most of the students gave positive responses to the application of learning-based learning model with average of pretest and posttest class percentage of experiment respectively 67,49% and 77,09% including strong category. Meanwhile, the average of pretest and posttest percentage of control class were 61.50% and 63.97%, respectively. Improvement of students ability in preparing RPP through the implementation of learning model project based learning average gain of 0.57 experimental class included in the category while the control class of 0.36 medium category; And the improvement of the students' ability in preparing the lesson plan that obtained the application of project based learning model is higher than that obtained the application of conventional learning model.